2014
DOI: 10.1186/1472-6750-14-18
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of a pectate lyase from Paenibacillus sp. 0602 in recombinant Escherichia coli

Abstract: BackgroundBiotechnological applications of microbial pectate lyases (Pels) in plant fiber processing are considered as environmentally friendly. As such, they become promising substitutes for conventional chemical degumming process. Since applications of Pels in various fields are widening, it is necessary to explore new pectolytic microorganisms and enzymes for efficient and effective usage. Here, we describe the cloning, expression, characterization and application of the recombinant Pel protein from a pecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Therefore, thermostable enzymes that have high catalytic activity under alkaline conditions are desirable for industrial degumming applications. For this purpose, alkaline Pels have been cloned from microbes (Berensmeier et al 2004;Boland et al 2010;Hatada et al 2001;Li et al 2014;Tardy et al 1997;Wang et al 2014;Zhang et al 2013) or from metagenomic DNA obtained from alkaline environment soils . In this study, BpPel from B. pumilus (ATCC 7061) was successfully engineered to improve its catalytic activity and thermostability for potential industrial application for ramie degumming process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, thermostable enzymes that have high catalytic activity under alkaline conditions are desirable for industrial degumming applications. For this purpose, alkaline Pels have been cloned from microbes (Berensmeier et al 2004;Boland et al 2010;Hatada et al 2001;Li et al 2014;Tardy et al 1997;Wang et al 2014;Zhang et al 2013) or from metagenomic DNA obtained from alkaline environment soils . In this study, BpPel from B. pumilus (ATCC 7061) was successfully engineered to improve its catalytic activity and thermostability for potential industrial application for ramie degumming process.…”
Section: Discussionmentioning
confidence: 99%
“…However, thus far, enzymatic degumming in the textile industry has been hampered by the high cost and partial degumming performance of the currently available enzymes. Microbial or enzymatic degumming processes are commonly combined with a chemical degumming process for maximal effect to meet the industrial requirements (Basu et al 2009;Li et al 2014). Due to the increasing interest and potential markets for enzymatic degumming, alkaline Pels have been obtained from various sources, cloned, and characterized (Berensmeier et al 2004;Kapoor et al 2001;Wang et al 2014;Zhang et al 2013); however, few Pels were found to be economically efficient for industrial applications owing to their low activity or poor stability under the required processing conditions (operation at moderate temperature [40-70°C] and alkaline pH [8][9][10][11]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, enzymes that are thermostable and active under alkaline conditions are desirable for industrial degumming applications. Because of the increasing interest in and potential market for enzymatic degumming, various alkaline Pels have recently been cloned and isolated from microbes (17,25,26,(28)(29)(30)(31)(32)(33)(34) or …”
mentioning
confidence: 99%
“…However, enzymatic degumming has not been widely used in the textile industry because of the high cost and unsatisfactory degumming efficiency of currently available enzymes. Thus, in the textile industry, microbial or enzymatic degumming processes are commonly combined with chemical degumming processes for maximal efficiency (24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation